Evaluation of Pre Nigeria Certificate in Education (Pre-NCE) Programme in Colleges of Education in Nigeria - Osokoya, Modupe (Institute of Advanced Engineering and Science, 2014)
The study evaluated the Pre-NCE programme within 2000-2004. Tyler’s goal-oriented approach with Scriven’s goal-free model was adopted. A total of 996 respondents from different cohorts of stakeholders participated in the study; six validated research instruments were used. The data gathered was analysed using descriptive statistics, t-test and multiple regressions. 59% of the students admitted to study Science, Language and Technical Education in Colleges of Education were products of the Pre-NCE programme, also 80% of them could transit beyond the 1st year of the NCE programme. The programme was rated as an effective intervention strategy for the production of pre-service teachers.DOI: http://dx.doi.org/10.11591/ijere.v3i1.3963